A one-pot strategy for coupling chalcogenide nanocrystals with 1D oxides for solar-driven processes. Issue 48 (30th September 2015) - Pathak, Pawan; Gupta, Satyajit; Resende, Aline C. S.; Subramanian, Vaidyanathan (Ravi)
Abstract : Deposition of 0D CdS on 1D TiO2 nanotubes. Abstract : This work presents a simple approach to the synthesis of CdS coatings on TiO2 nanotubes (T_NTs) and to form a heterostructured composite. A non-pressure based, single precursor one-pot approach performed at a temperature of 160 °C is used to assemble CdS on the TiO2 surface. Surface characterization using microscopy, X-ray diffraction, and elemental analysis indicates the formation of dense hexagonal 〈002〉 CdS nanocrystals along the nanotube walls and inter-tubular spacing. Optical measurements indicate that the CdS absorbs in the visible region and demonstrates a red shift with increased loading: up to 12 nm red shift is noted when the precursor concentration is increased from 0.1–3 mM. The 0D CdS/1D T_NT was also tested as an anode in a photoelectrochemical cell. The electrode produced the highest reported photocurrent of 9.3 mA cm −2 under UV-visible illumination when compared with similar systems. The method may be used in assembling efficient photoanodes for multifunctional solar-driven processes.